Effects of long-term drainage on vegetation - Sinyutkina; A. A.; Gashkova; L. P.; Kharanzhevskaya; Yulia A.; Magur; M. G.; Voistinova; E. S.; Ivanova; Chudinovskaya; et al. (IOP Conference Series: Earth and Environmental Science, 2018)
In this study we determine the influence of a long-term drainage on the vegetation surface topography hydrology and water chemistry of the north-eastern drained part of the Great Vasyugan Mire. Many studies have shown an increase in the projective coverage of V. Uliginosum A. polifolia P. schreberi P. Strictum and D. polysetum Cladonia stellaris and Cladonia rangiferina and a decrease in the projective coverage of C. calyculata and L. palustre S. angustifolium S. magellanicum. In the peat core in comparison with archival data (1985) an increase in the degree of peat decomposition by 5-10% in the top 10-100 cm layer is noted which may be due to the partial degradation of the peat deposit as a result of dehumidification. The microrelief is characterized by a decrease in the proportion of heights at the middle surface from 44 to 37% and the presence of steep slopes between the positive and negative forms of the microrelief. A decrease in the water table levels of bog waters and an increase in the amplitude of the oscillation are noted. In the chemical composition of the drained bog we note an increase in the concentrations of the main ions by 6-38% as well as DOC by 13% Pb by 9% Cu by 46% and Zn by 215%. In the river waters there is an increase in NO3 − by 11% NH4 + by 26% SO4 2-by 36% Fetotal by 89% and DOC by 17% no increase in the concentrations of Pb Cu Zn is observed.